2001
DOI: 10.1002/ijc.1566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytarabine and various anthracyclins on platelet activation: Characterization of in vitro effects and their possible clinical relevance in acute myelogenous leukemia

Abstract: Previous in vitro studies have demonstrated that normal platelets and platelet-released mediators can alter in vitro characteristics of human acute myelogenous leukemia (AML) blasts. To further investigate whether platelets can be expected to adhere to and thereby affect AML blasts through their release of soluble mediators into a common microenvironment, we investigated (i) the effects on platelet activation by cytotoxic drugs commonly used in AML therapy; (ii) the occurrence of circulating activated platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…The results presented here, demonstrate that leukemia cell lines promote platelet activation, supporting the notion that the leukemic bone marrow may possibly activate newly formed platelets, perhaps contributing to leukemic thrombocytopenia [31]. This notion is also congruent with the observation by Foss B and colleagues [32] that platelets can adhere to acute myeloid leukemia blasts, and their hypothesis that platelets and leukemic blasts share in vivo microenvironments. In addition, contrary to what has been reported for solid tumor cell lines, MSC [16,17] and leukemic blasts [18], platelet contents did not affect the proliferation of OCI-AML3 or MOLT cells, suggesting that the proliferative and the chemoprotective effects of platelets may be mediated by different mechanisms in a cell context dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…The results presented here, demonstrate that leukemia cell lines promote platelet activation, supporting the notion that the leukemic bone marrow may possibly activate newly formed platelets, perhaps contributing to leukemic thrombocytopenia [31]. This notion is also congruent with the observation by Foss B and colleagues [32] that platelets can adhere to acute myeloid leukemia blasts, and their hypothesis that platelets and leukemic blasts share in vivo microenvironments. In addition, contrary to what has been reported for solid tumor cell lines, MSC [16,17] and leukemic blasts [18], platelet contents did not affect the proliferation of OCI-AML3 or MOLT cells, suggesting that the proliferative and the chemoprotective effects of platelets may be mediated by different mechanisms in a cell context dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…48,61 It is not possible to judge whether these variations reflect altered bone marrow vessel density because bone marrow biopsies for examination of vessel density after chemotherapy were not available, but the hypothesis is supported by a previous work describing an association between response to induction therapy and reduction of microvessel density in the bone marrow. 62 We recently reported that AML chemotherapy can activate platelets and increase platelet adhesion to AML blasts, 63 and these events may modulate the direct effects of cytotoxic drugs on malignant cells. Our results describing an effect of intensive chemotherapy on systemic angiogenic regulation is another example of indirect chemotherapy effects that may be clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets derived from acute and chronic myeloid leukemia (AML and CML) patients tend to have impaired platelet responsiveness to physiological agonists [76], may have platelet storage pool deficiency [77]; and commonly for AML, disease and treatment-induced thrombocytopenia [78,79]. Nonetheless, TPO has been shown to induce aggregation of CML platelets from chronic phase patients with cytogenic remission [80], and AML blasts have been shown to bind platelets and induce PDGF secretion [79,81] to provide protection from chemotherapy-induced apoptosis to adenocarcinomas [28].…”
Section: Accepted Manuscriptmentioning
confidence: 99%